Structural Reform, Stabilization, and Growth in Turkey - Kopits, George (Occasional Papers; Occasional Paper ;, 1987)
Following a severe balance of payments crisis in the late 1970s, in January 1980 Turkey embarked on a far reaching stabilization and structural adjustment program.